2009
DOI: 10.1002/marc.200900087
|View full text |Cite
|
Sign up to set email alerts
|

‘Click’ Functionalization of Cryogels Conveniently Verified and Quantified Using High‐Resolution MAS NMR Spectroscopy

Abstract: Chemical modification reactions of alkyne containing polyHEMA-based macroporous network structures (cryogels) by Cu(I) catalyzed azide-alkyne 'click' cycloaddition reactions and their monitoring and quantification with high-resolution magic angle spinning (hr-MAS) NMR spectroscopy are reported. Complete conversion is obtained when benzylazide is reacted with the grafted alkyne function, but only partial conversion is observed when using azide-modified poly(ethylene glycol) (PEG-N(3) ). Subsequent addition of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…As a complementary method to IR, Raman spectroscopy can reveal other functional groups (such as C-Cl and C≡N) that can be difficult to detect by IR [302][303]. Moreover, solid state [304][305], gel phase [306][307] and high-resolution magic angle spinning (HRMAS) NMR [308][309][310][311] techniques can be quite successfully applied to detect the functional groups and monitor reactions on particles. Availability of probes, operator experience and need of a suitable solvent for the analysis can be the parameters to tackle.…”
Section: Chemical Analysismentioning
confidence: 99%
“…As a complementary method to IR, Raman spectroscopy can reveal other functional groups (such as C-Cl and C≡N) that can be difficult to detect by IR [302][303]. Moreover, solid state [304][305], gel phase [306][307] and high-resolution magic angle spinning (HRMAS) NMR [308][309][310][311] techniques can be quite successfully applied to detect the functional groups and monitor reactions on particles. Availability of probes, operator experience and need of a suitable solvent for the analysis can be the parameters to tackle.…”
Section: Chemical Analysismentioning
confidence: 99%
“…NMR spectroscopy has been more frequently catalysed azide-alkyne "click" cycloaddition reactions using high-resolution magic angle spinning (MAS) NMR spectroscopy. The authors observed complete conversion when benzylazide molecules reacted with the grafted alkyne functions, but only partial conversion was observed when they used azide-modified poly(ethylene glycol) [164]. Subsequent addition of benzylazide consumed all remaining alkyne groups.…”
Section: Low-temperature 1 H Nmr Spectroscopy Tsdc and Quantum Chemimentioning
confidence: 99%
“…All chemical modifications were easily monitored at each stage using the MAS NMR spectroscopy. The alkyne functionality and the resulting triazole ring gave well resolved 1 H resonances to monitor and quantify the progress of such "click" reactions in general [164]. However, the authors did not use the NMR method to study the textural characteristics of the synthesised cryogels.…”
Section: Low-temperature 1 H Nmr Spectroscopy Tsdc and Quantum Chemimentioning
confidence: 99%
“…[30,31] Other HR-MAS studies observed the impact of cross-linking in solvent swollen poly(amidoamine) polymers, the nature of water interactions in these same class of polymers, [32,33] or the cross-linking performance in silicon-containing soybean-oil copolymers. [34] HR-MAS NMR has also been used to study the functionalization of poly hydroxyethyl methacrylate (HEMA) cryogels, [35] cyclomaltoheptaose polymers, [36] the synthesis of hyper-branched bis (hydroxymethyl) propionic acid (bis-MPA) polymers as a function of catalysts, [37] and polymers for nanoparticle stabilization. [38] HR-MAS NMR has found use in investigation of porous polyalkylvinyl ether polymer particles being used for stationary phases in chromatographic applications.…”
Section: Polymersmentioning
confidence: 99%